Purchase intention of cruelty-free cosmetics : the effects of brand type and cruelty-free labels - Pülm, Caroline (2021)
In the last years, ethical consumption has received growing attention, with more consumers demanding product alternatives that have less detrimental effects on the environment, people, and animal welfare. This trend has led to the introduction of cruelty-free cosmetics - products that have not been tested on animals. This study examines consumers’ intention to purchase cruelty-free cosmetics and evaluates the influence of brand type and cruelty-free labels using the example of shampoo. For this purpose, an online questionnaire was conducted. The study follows a 2x3 cross-sectional design and exposes participants to one of six different stimuli, differing in brand type and cruelty-free label type. Furthermore, the study builds on the theory of planned behaviour, therefore, participants’ attitude towards cruelty-free cosmetics was also measured. The results show a significant preference for national brand shampoo over private label shampoo. Moreover, shampoo, denoted with a cruelty-free label, exerts higher purchase intention than the non-labelled counterparts. However, label type (certified vs. uncertified) does not yield significant differences. Furthermore, the study did not find any mediating effect of attitude on purchase intention. The findings indicate a high intention to purchase cruelty-free cosmetics, especially for national brand products. Consequently, companies should add cruelty-free cosmetics to their product portfolio. However, in the current state, consumers lack sufficient knowledge about cruelty-free cosmetics. Therefore, companies need to educate their consumers and team up with third parties to receive official accreditation.